Dynamics of the Cu/CeO2 catalyst during methanol steam reforming. Issue 23 (10th November 2022) - Jin, Shiqing; Li, Didi; Wang, Zhen; Wang, Yiming; Sun, Li; Zhu, Minghui
Abstract : Supported Cu/CeO2 catalysts with various loadings prepared by a deposition–precipitation method are investigated by a series of in situ characterization techniques: structures of active sites dynamically change in response to environmental conditions. Abstract : Supported Cu/CeO2 catalysts with various loadings prepared by a deposition–precipitation method are thoroughly investigated with a series of in situ characterization techniques. The catalyst surface contains metallic Cu 0 and interfacial sites, with the latter acting as the key active sites for the methanol steam reforming reaction. Moreover, the structures of both sites dynamically change in response to various environmental conditions. The Cu 0 sites on larger Cu particles are more prone to oxidation than those on small ones, and the Cu–Ov –Ce interfacial sites are partially oxidized during the MSR reaction.